Taking the village online : mothers, motherhood, and social media (Demeter Press, 2016)
"The rise of social media has changed how we understand and enact relationships across our lives, including motherhood. The meanings and practices of mothering have been significantly impacted by the availability of online mother groups (Facebook, Twitter, Instagram) as well as internet resources intended to 'enhance' and inform maternal experience and self-concept (ex. pinterest, YouTube). The village that now contributes to the mothering experience has grown exponentially, granting mothers access to interactional partners and knowledge never before available. This volume of works explores the impact of social media forms on our cultural understandings of motherhood and the ways that we communicate about the experience and practice of mothering. The contributing authors in this anthology address diverse topics in mothering and social media, including framing of stepmothers in online forums, mothering in the digital diaspora, the construction of the "bad mother" on Twitter, immersive gaming and parenting classes, virtual mother outlaws, alternative mothering websites, feminist parenting, and more. While the works are primarily rooted in critical and feminist perspectives, a variety of methodologies and approaches to studying mothering and social media are represented in this text, and encourage a robust and thoughtful examination of the role of interactive media in the maternal experience. Lorin Basden Arnold, Ph. D. is a family communication and gender scholar. Her recent scholarly work has primarily related to understandings and enactments of motherhood. Her work has appeared in recent Demeter editions, including Intensive Mothering: The Cultural Contradictions of Modern Motherhood and What's Cooking Mom? Narratives about Food and Family. She is the Provost and Vice President for Academic Affairs at the State University of New York, New Paltz. BettyAnn Martin is a doctoral candidate in Educational Sustainability at Nipissing University, North Bay, ON. She.